2016
DOI: 10.4209/aaqr.2016.03.0120
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter, Ozone, and Nitrogen Species in Aged Wildfire Plumes Observed at the Mount Bachelor Observatory

Abstract: During the summer of 2012 and 2013, we measured carbon monoxide (CO), carbon dioxide (CO 2 ), ozone (O 3 ), nitrogen oxides (NO x ), reactive nitrogen (NO y ), peroxyacetyl nitrate (PAN), aerosol scattering (σ sp ) and absorption, elemental and organic carbon (EC and OC), and aerosol chemistry at the Mount Bachelor Observatory (2.8 km above sea level, Oregon, US). Here we analyze 23 of the individual plumes from regional wildfires to better understand production and loss of aerosols and gaseous species. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 62 publications
1
85
1
Order By: Relevance
“…From the scatter plots of multiple measurements of Y plotted against X, we can calculate the enhancement ratio (ΔY/ΔX) by taking the slope of a Reduced Major Axis (RMA) linear regression. A comparison of different approaches to get the enhancement ratio is shown in the paper by Briggs et al (2016). These enhancement ratios, along with results from similarly aged Siberian plumes observed in North America, are summarized in Table 1.…”
Section: Enhancement Ratios Of the Siberian Plumementioning
confidence: 99%
See 1 more Smart Citation
“…From the scatter plots of multiple measurements of Y plotted against X, we can calculate the enhancement ratio (ΔY/ΔX) by taking the slope of a Reduced Major Axis (RMA) linear regression. A comparison of different approaches to get the enhancement ratio is shown in the paper by Briggs et al (2016). These enhancement ratios, along with results from similarly aged Siberian plumes observed in North America, are summarized in Table 1.…”
Section: Enhancement Ratios Of the Siberian Plumementioning
confidence: 99%
“…However, if the plume warmed up (i.e., via descent), then PAN would decompose back to NO x and ozone formation can take place. For comparison, Briggs et al (2016) looked at regional fires observed at MBO during summer 2012 and 2013 and found that PAN comprised 25-57% of the total reactive nitrogen. Table S1 quantifies the reactive nitrogen speciation for AC plumes 1, 2, and 3.…”
Section: Enhancement Ratios Of the Siberian Plumementioning
confidence: 99%
“…Bachelor Observatory. Briggs et al (2016) found little difference between Δσ scat /ΔCO and ΔNO y /ΔCO NERs calculated using the three methods if the enhancement of the species in the plumes was large relative to the background concentrations (σ scat is the aerosol scattering coefficient, which is well correlated to PM 2.5 ). Large differences were found for ΔO 3 /ΔCO and ΔCO/ΔCO 2 , where the enhancement is small relative to the background.…”
Section: Introductionmentioning
confidence: 95%
“…Normalized enhancement ratios (NERs), also known as normalized excess mixing ratios, are a good way to help identify the source of a pollution plume observed at ambient monitoring sites (Andreae and Merlet, 2001;Briggs et al, 2016). During a pollution or smoke event in which concentrations of two species (X and Y) increase substantially above background levels, NERs relate the excess concentrations of a target species X with that of a reference species Y (NER = ΔX/ΔY, where Δ is the enhancement over background concentrations).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation